The Information Status of Old English Constructions with Titles and Proper Names - Elżbieta Sielanko-Byford (LingBaW)
The paper examines the information status of Old English structures consisting of proper names and titles. The nominal constructions under discussion fall into three categories: the Ælfred cyning type of structure, where the title appears without any determiner and follows the proper name, the Ælfred se cyning type, where the title appears with a determiner and follows the proper name, and the se cyning Ælfred type, where the title with a determiner precedes the proper name. It is demonstrated that the se cyning Ælfred construction is mainly used anaphorically: an overwhelming majority of the examples of the structure in the Old English texts examined here refer back to an entity mentioned in the preceding discourse. Moreover, most of the antecedents of the se cyning Ælfred structures appear to be local, that is they occur in the same or in the immediately preceding structural unit. It is argued that the anaphoric nature of the se cyning Ælfred constructions may be responsible for their distribution in Old English texts.